Occurrence Of Heavy Metal Resistance In Sinorhizobium Sp. Isolated From Root Nodules Of Fenugreek, Treated With Tannery Effluent (Applied Biological Research, 2020)
The aim of present study was to initiate preliminary work on heavy metal  contamination in farm soil (contaminated with processed tannery effluent) and its potential influence on the development of metal resistance among N2- fixing bacterium, Sinorhizobium sp. Contaminated plant samples were  analyzed for various metals and minimum inhibitory concentration (MIC) of  metals was determined. Fenugreek (Trigonella sp.) plants revealed  accumulation of these metals in root and leaves. Sinorhizobium sp. were  isolated (25) from the root nodules of fenugreek-treated with processed tannery wastewater and characterized morpho-biochemically. All isolates  were evaluated for their resistance against Cr3+, Cr6+, Cd2+, Cu2+, Zn2+ and  Ni2+. The maximum MIC of 1600 µg mL-1 was noticed against Cr3+ in 64%  isolates. Among all the isolates, the lowest MIC of 25 µg mL-1 was detected  against Ni2+. Some metal resistant isolates were evaluated for their resistance  against frequently used antibiotics viz., tetracycline, ampicillin, gentamycin,  kanamycin, chloramphenicol and nalidixic acid. About 46% Sinorhizobium isolates were resistant to nalidixic acid whereas 26.6% showed resistance to  ampicillin and kanamycin. The isolates demonstrated confluent growth upto  a salt concentration of 3%; whereas isolates (SM17, SM24) tolerated 10%  NaCl. Acidic pH eliminated almost all the test population and neutral pH had  no suppressive effect on growth while majority were tolerant to pH 9.
Keywords: Fenugreek; metal resistance; Sinorhizobium; tannery effluent